Best Answer

-4x - 1 = -7

add 1 to both sides to get...

-4x = -6

divide both sides by -4 to get

x = 1.5

Q: -4x - 1 equals -7

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

4x - 7 = 1 Therefore, 4x = 8 x = 8/4 x = 2

sqrt(4x+7) -4 = sqrt(4x-1) squared : (sqrt(4x+7) -4)2 = 4x-1 (4x+7) - 2x4xsqrt(4x+7) +16 = 4x-1 -8xsqrt(4x+7) = -24 sqrt(4x+7) = -24/-8 = 3 squared : 4x+7 = 32 = 9 4x = 9-7 = 2 then x=1/2

4x-1 = 6x-15 4x-6x = 1-15 -2x = -14 x = 7

(2, 7)

4x-5=7 4x=12 x=3

Related questions

3x = 7-4x 3x+4x = 7 7x = 7 x = 1

3x = 7 - 4x 3x + 4x = 7 - 4x + 4x 7x = 7 7x/7 = 7/7 x = 1

4x - 7 = 1 Therefore, 4x = 8 x = 8/4 x = 2

y= -4x-7 y=3x 3x= -4x-7 3x+4x=7 7x=7 x=1

If 4x + 7 = 3... then x must equal -1

4x - 1 = 7 Add 1 to both sides: 4x = 8 Divide both sides by 4: x = 2

y = 2x-5 4x-y = 7 => y = 4x-7 2x-5 = 4x-7 2x-4x = 5-7 -2x = -2 x = 1 Therefore by substituting: x = 1 and y = -3

sqrt(4x+7) -4 = sqrt(4x-1) squared : (sqrt(4x+7) -4)2 = 4x-1 (4x+7) - 2x4xsqrt(4x+7) +16 = 4x-1 -8xsqrt(4x+7) = -24 sqrt(4x+7) = -24/-8 = 3 squared : 4x+7 = 32 = 9 4x = 9-7 = 2 then x=1/2

(A): 4x + y = 7 (B): 2x - 3y = -7 2*(B) 4x - 6y = -14 Subtract from (A) 7y = 21 Divide both sides by 7: y = 3 Substitute in (A): 4x + 3 = 7 ie 4x = 4 or x = 1 Answer: x = 1 , y = 3

x=2/7

4x-1 = 6x-15 4x-6x = 1-15 -2x = -14 x = 7

If: 5x = 4x+7 Then: 5x-4x = 7 And: x = 7